A medical digital library to support scenario and user-tailored information retrieval. - Chu, W.W (IEEE Transactions on information technology in biomedicine)
Current large-scale information sources are designed to support general queries and lack the ability to support scenario-specific information navigation, gathering and presentation. As a result, users are often unable to obtain desired specific information within a well-defined subject area. Today's information systems do not provide efficient content navigation, incremental appropriate matching or content correlation. We are developing the following innovative technologies to remedy these problems: (1) scenario-based proxies, enabling the gathering and filtering of information customized for users within a pre-defined domain; (2) context-sensitive navigation and matching, providing approximate matching and similarity links when an exact match to a user's request is unavailable; (3) content correlation of documents, creating semantic links between documents and information sources; and (4) user models for customizing the retrieved information and the presentation of results. A digital medical library is currently being constructed using these technologies to provide customized information for the user. The technologies are general in nature and can provide custom and scenario-specific information in many other domains (e.g. crisis management).